O papel da melatonina no hipotálamo lateral/área perifornicial (LH/PFA) na resposta ventilatória à hipercapnia em ratos durante o sono e vigília - Salata, Bruno (2021)
The lateral hypothalamus and perifornicial area (LH/PFA) contain neurons involved in the central hypercapnic ventilatory response. Orexinergic neurons have been attributed to the CO2 chemosensitive function of this region, but much still needs to be investigated regarding to local neurochemical mechanisms, in LH/PFA, in the modulation of the central hypercapnic chemoreflex. Evidence points to the involvement of melatonin in the modulation of the activity of LH/PFA neurons, however the possible participation of melatonin, acting on LH/PFA, in the central hypercapnic chemoreflex had not yet been investigated. Thus, we recorded pulmonary ventilation, EEG, EMG and body temperature (Tb) in non-anesthetized rats, in a whole-body plethysmography system and studied the effects of the microinjection of melatonin (20mM) into the LH/PFA of conscious rats on ventilation in room air and in 7% CO2. The microinjection of melatonin increased the CO2 ventilatory responses of rats during wakefulness. Our data suggest that melatonin in the LH/PFA contributes to the hypercapnic ventilatory response in unanesthetized rats, in a state-dependent manner.